TEACHING PRACTICES IN THE NEW NORMAL: QUALITATIVE INQUIRY (SRI LANKA CASE) - Vivek, Ramakrishnan; Nanthagopan, Yogarajah; Piriyatharshan, Sarmath; Krupskyi, Oleksandr P. (Advanced Education, 2023)
The public education system shifted towards one centered on information technology due to the COVID-19 epidemic. Hence, in recent years, online learning has emerged as a substantial curriculum component at several educational institutions in Sri Lanka. The present investigation explores the pedagogical practices in Sri Lankan government universities in the new normal via a qualitative approach by interviewing eight instructors in eight public universities. The findings revealed that the pedagogy has shifted to an online context with the pandemic, and the education system continuously applies online teaching, assessment, and evaluation techniques. Teachers and students initially encountered various issues in the new normal, including technical difficulties, economic conditions, and a lack of available resources for integrating IT into the education pedagogy. Hence, current practices should continue facilitating digital infrastructure and blended approaches for better outcomes. The authors recommend that policymakers and authorities take high responsibility for building an effective IT-based strategy. It is vital to train educators and encourage them to fully utilize the recent movement towards online instruction by supplying all the necessary technological skills. Training educators and encouraging them to utilize the recent movement towards online instruction entirely is vital by supplying all the necessary technological skills. The government should provide essential infrastructure and facilities to institutions while working toward creating a welcoming atmosphere within universities. Giving encouragement and financial aid to students is critical to alleviating student pressures while transitioning to online learning methods. Policymakers must consider the significance of the human component and realize that technology alone cannot solve every problem. The present transition in the educational system demands implementing a strategic framework to identify the strengths and address the shortcomings.